(9x^4+7x^2-6x-15) - (3x^3-7x^2+6x-15) = 9x^4 - 3x^3 +14x^2 - 12x
2. I hope I am interpreting this correctly
(9m4n2 - 13m3n3 + 11m2n4) +(-4m2-n4-3m4n2-m3n3) = 6m4n2 - 14m3n3 + 7m2n4 - n4
(9m4n2 - 13m3n3 + 11m2n4) - (-4m2 - n4 - 3m4n2 - m3n3)= 12m4n2 -12m3n3 + 15m2n4 + n4
3. and 4. Dear Ma: now that you've seen how to work a couple of these, why not try the next two on your own. If you run into any difficulty, send me a message and I'll help you.
5. (2x3 - 4x2 -7x +19) + ? = (x2 + 3x +24)
You can treat the question mark just as if it were some other variable.
? = (x2 + 3x +24) - (2x3 - 4x2 -7x +19)
? = -2x3 +5x2 +10x +5